A novel ladderlectin from hybrid crucian carp possesses antimicrobial activity and protects intestinal mucosal barrier against Aeromonas hydrophila infection. Issue 124 (May 2022) - Feng, Chen; Liu, Xiaofeng; Tang, Yiyang; Feng, Mengzhe; Zhou, Zejun; Liu, Shaojun
Abstract: Ladderlectin is a pattern recognition receptor (PRR) in fish that is critical for rapid detection of bacteria in vitro, but the immunological function of ladderlectin in vivo is essentially unknown. In this study, we examined the expression and function of a ladderlectin homologue (WR-ladderlectin) from hybrid crucian carp. WR-ladderlectin contains 157 amino acids and possesses the conserved C-type lectin domain. WR-ladderlectin is mainly expressed in the intestine and is upregulated by bacterial infection. Recombinant WR-ladderlectin (rWR-ladderlectin) agglutinated Aeromonas hydrophila and Escherichia coli . rWR-ladderlectin also bound the A. hydrophila and E. coli in a protein dose-dependent manner. As well as its ability to bind bacterial cells, rWR-ladderlectin displayed apparent bactericidal activity against A. hydrophila and E. coli in vitro . When introduced in vivo, rWR-ladderlectin induced significant expression of the antimicrobial molecules and tight junctions in the intestine. In addition, rWR-ladderlectin prevented significant decrease in the length of intestine villus and enhanced the host's resistance to bacterial infection. These results indicate that WR-ladderlectin is a classic pattern recognition molecule that protects intestinal mucosal barrier against bacterial infection. Highlights: mRNA expression of WR-ladderlectin was significantly induced by bacterial challenge. WR-ladderlectin exhibited bactericidal activity to Aeromonas hydrophila and Escherichia coli. WR-ladderlectin could enhance intestinal barrier and resistance against bacterial infection.